Production of coffee fruits (Coffea arabica L.) in different positons and orientation of plagiotropic shoots - Sandy, Eder Carvalho; Botelho, Cesar Elias; Carvalho, Alex Mendonça de; Guimarães, Rubens José; Carvalho, Gladyston Rodrigues; Magalhães, Marcelo Murad (Coffee Science - ISSN 1984-3909, 1970)
This paper aimed at to evaluate the fruit production in different positions of coffee plagiotropic shoot (Coffea arabica L.), during eight months. Measurements started in October 21 taking five different regions of eight shoots located in the central region of a plant belonging to the cultivar of Rubi MG 1192; located at the Coffee Section from the Federal University of Lavras. The experimental design used was random blocks disposed in factorial scheme, 2x 4x 8, composed by two positions(upper third and lower third), four orientations (east sunrise, west sunset, north and south) and eight evaluations time (from October 2005 to May 2006), totalizing 64 treatments, containing 10 replicates and one plant per plot. There was a reduction in fruit number per shoot during the development and this fact was more proeminent in shoots located in the inferior part of the plant and in period from December to January. The orientations North, South, East and West did not influence the number of fruits during the development.